Getting Sweetpotato Varieties to Farmers Faster: The Accelerated Breeding Scheme (ABS) - International Potato Center (2014)
Solid evidence generated since 2005 in Peru and Mozambique has shown that the ABS efficiently reduces the time (8 to 4-5 years) from crossing to varietal release within a given sweetpotato population.